A case report of steroid resistant cardiac sarcoidosis successfully managed with methotrexate - Grabowska, Olga; Martusewicz-Boros, Magdalena M; Piotrowska-Kownacka, Dorota; Wiatr, Elżbieta (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Up to one fourth of sarcoidosis patients may have cardiac involvement, what is potentially a life-threatening condition and requires aggressive treatment. Corticosteroids are generally effective in cardiac sarcoidosis, however may have significant short and long term adverse effects. We present a case of a 42-year-old male, who was diagnosed with pulmonary and cardiac sarcoidosis. He was treated initially with corticosteroids and satisfactory improvement was achieved in the lungs but not in the heart. Methotrexate was added as a second line therapy, being beneficial for the heart as well as steroid sparing agent. Cardiac improvement was documented during serial CMR imaging.